2010
DOI: 10.1016/j.virol.2010.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of functional domains of Chandipura virus Nucleocapsid protein involved in oligomerization and RNA binding: Implication in viral genome encapsidation

Abstract: Chandipura virus, a member of the vesiculovirus genera, has been recently recognized as an emerging human pathogen. Previously, we have shown that Chandipura virus Nucleocapsid protein N is capable of binding to both specific viral leader RNA as well as non-viral RNA sequences, albeit in distinct monomeric and oligomeric states, respectively. Here, we distinguish the regions of N involved in oligomerization and RNA binding using a panel of deletion mutants. We demonstrate that deletion in the N-terminal arm co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 44 publications
7
35
0
Order By: Relevance
“…Out of these eight interactions, five novel interactions (G-N, N-M, G-G, M-M and M-G) were observed, of which three have already been reported for CHPV. The three known interactions observed here (N-N, P-N and P-P) were in concordance with the earlier studies, and thus served as positive controls for our interaction analysis [26,30,33]. Amongst the novel interactions, the G-N protein pair has not been documented for members of the family Rhabdoviridae and can be investigated further to decipher its role in the structural assembly of the virus during various stages of the viral life cycle.…”
Section: Bait-strep Proteins Bound To Strep-tactin Elisa Platessupporting
confidence: 88%
See 1 more Smart Citation
“…Out of these eight interactions, five novel interactions (G-N, N-M, G-G, M-M and M-G) were observed, of which three have already been reported for CHPV. The three known interactions observed here (N-N, P-N and P-P) were in concordance with the earlier studies, and thus served as positive controls for our interaction analysis [26,30,33]. Amongst the novel interactions, the G-N protein pair has not been documented for members of the family Rhabdoviridae and can be investigated further to decipher its role in the structural assembly of the virus during various stages of the viral life cycle.…”
Section: Bait-strep Proteins Bound To Strep-tactin Elisa Platessupporting
confidence: 88%
“…The identified interactions can be classified on the basis of the location of these proteins in the virus as core proteins (N, P) and membrane proteins (M, G). Previous studies have demonstrated interactions between the elements of the CHPV ribonucleoprotein (RNP) complex by deletion mutations and aggregation experiments in bacterial or eukaryotic systems [26,30,33]. In the present study, the identification of these previously reported interactions between the N and P proteins (selfassociation and inter-protein interactions) validate our approach to PPI analysis.…”
Section: Discussionsupporting
confidence: 69%
“…However, the rhabdoviral N protein alone is incapable of performing this task. According to numerous studies, N protein when expressed alone forms large insoluble aggregates [14][16] and binds to short cellular RNAs non-specifically [17][21]. Conversely, when co-expressed with the P protein, a major fraction of the N protein is rendered soluble and free of non-specific RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Also, though the mutation occurred within a phosphorylation motif, the putative phosphorylation site 40Thr was conserved. Further, the homologous substitution Glu364Asp in the CHPV isolates was located within the C-terminal region (320–422 aa) and might not affect RNA recognition [16]. However, as it mapped on to a probable T-cell epitope, it needs to be experimentally verified for pathogenicity.…”
Section: Discussionmentioning
confidence: 99%